AN ANALYSIS OF POLITICAL METAPHOR IN HEADLINE NEWS OF THE JAKARTA POST - Suci Fitriani; Jismulatif Jismulatif; Muhammad Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of the research is to find out the type of conceptual metaphor that is most frequently used in the headlines of the political news posted online on the website of The Jakarta Post. This research is conducted by using qualitative research which is descriptive analysis. The data collection technique of this research is a study document and uses MIP (Metaphor Identification Procedure) as a method to analyze the data. The result shows that there are 183 headlines of political news using structural metaphor, 71 headlines of political news using ontological metaphor, and 31 headlines of political news using orientational metaphor. It is concluded that the structural metaphor is the most frequently used in headline news of The Jakarta Post, which mostly associated the concept of politics with the concept of war.Keywords: Conceptual Metaphor, Politics, Headline News, The Jakarta Post.